Diagnostic Efficacy of Deeper Sections in Routine Oral Histopathology Practice: a Retrospective Study - Achla Bharti Yadav; Mala Kamboj; Anjali Narwal; Anju Devi (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Histopathology is a gold standard diagnostic tool for oral lesions. Nonspecific and overlapping microscopic features often pose diagnostic challenges in routine practice. In such conditions, deeper sections have utility to enhance the sensitivity and accuracy of the diagnosis. Purpose: To analyze the percentage of deeper sections requested and to evaluate the diagnostic efficacy of these deeper sections in routine oral histopathology practice. Additionally, the utility of deeper sections in specific oral lesions have also been evaluated. Materials and Method: A total of 850 cases from the archives of Department of Oral Pathology and Microbiology, were analyzed, and 106 cases with deeper sections were selected. Out of 106, 82 cases were accepted for our analysis and 24 were rejected as deeper sections were done due to staining errors or folding of tissue. The present retrospective study involves comparison of initial histological findings with those seen in deeper sections of same specimen. Results: Deeper sections improved the diagnosis of 48 cases (58.54%). Remaining 31 cases (38%) showed the same histological features, whereas in 3 cases (3.66%), initial sections were good as compared to deeper sections. Out of 22 cases of provisional hyperkeratotic/ dysplastic lesion, 16 (72.72%) showed change in diagnosis, i.e. from mild to severe dysplasia or from dysplasia to carcinoma. A total 12 out of 17 (70.59%) cases of odontogenic lesions were non- diagnostic or showed minimal characteristic features on initial sections, but their deeper sections revealed clearly identifiable features and some of them also showed cystic lesion turning into tumor pathology. Conclusion: This study highlights the diagnostic efficacy of deeper sections and their contribution towards providing accurate and more descriptive features.